Global franchising operations management : cases in international and emerging markets operations - Alon, Ilan. (Upper Saddle River, N.J. : FT Press/Pearson, 2012)
Franchising, already a $740 billion business in the United States, is now experiencing rapid growth worldwide. In this book, the world's leading expert on global franchising helps companies decide whether to franchise outside the United States, identify their best global opportunities, and understand the unique challenges of franchising in emerging markets and developing countries. Through multiple case studies, Dr. Ilan Alon and a team of expert contributors offer a panoramic and up-to-date view of franchising around the world. They introduce operations management systems from diverse industries, nations, and regions, presenting both franchiser and franchisee perspectives. The author candidly discusses both successes and failures, identifies key success factors, highlights obstacles, and demonstrates innovative ways to overcome them.
San Francisco coffee house : An American style franchise in Croatia / Ilan Alon, Mirela Alpeza, and Aleksander Erceg -- Trying to create a stir : Opening a coffee shop in Korea / Gyewan Moon and Allen H. Kupetz -- International marketing and franchising at Marks & Spencer / Ilan Alon -- Estimating demand in emerging markets for Kodak Express / David M. Currie and Ilan Alon -- Ruth's Chris Steak House : The high stakes of international expansion / Allen H. Kupetz and Ilan Alon -- Master international franchising in China : The Athlete's Foot, Inc. (Part A) / Amber Xu and Ilan Alon -- Master international franchising in China : The Athlete's Foot, Inc. (Part B) / Amber Xu and Ilan Alon -- Social entrepreneurship and sustainable farming in Indonesia / Ilan Alon and Eve Misati -- Final reflections and epilogues.
Includes bibliographical references and index.
Keywords: Franchises (Retail trade); International trade; Franchises (Retail trade) -- Case studies